THE IMPORTANCE OF PROBLEM EDUCATIONAL TECHNOLOGIES ORGANIZED IN THE HIGHER EDUCATION SYSTEM IN EDUCATION - Kinjayeva Gulbakhor Sattorqulovna (Journals Park Publishing, 2024)
One of the effective teaching technologies in the modern education system is problem-based learning. Problem-based learning corresponds to the goals of creative and active education of the individual. The essence of problem-based learning is the independent acquisition of new knowledge by creating a problem situation.
Keywords: problem situation, problem, problem task, problem lecture, problem teaching, joint problem lecture, problem seminar, problem teaching, problem situation, effective technology, training.